(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Encontros Bibli Vol. 17, n. 34 (2012) Link de acesso ao número http://www.periodicos.ufsc.br/index.php/eb/issue/view/1896/showToc